(1.)  (5b + 4c + 8d) + (8b - 7c - 6d) + (3b - 4c)

[here is the problem]

=      16b - 7c + 2d      combine like terms

result:   16b - 7c + 2d

(2.)   (7x - 2y + 5z) + (8y - 9z) + (7x - 5y)

[here is the problem]

=      14x + y - 4z          combine like terms

result:  14x + y - 4z

(3.)   (5x + 7y - 10) + (8y - 2x + 3) + (2x - 10y + 4)

[here is the problem]

=      5x + 5y - 3              combine like terms

result:  5x + 5y - 3

(4.)   (4a2 - 5ab - 6b2) + (10ab - 6a2 - 8b2) + (10b2 - 3a2 - 7ab)

[here is the problem]

=       -5a2 - 2ab - 4b2           combine like terms

result:  -5a2 - 2ab - 4b2

(5.)  (a - b + c) + (b - c - a) + (c - a + b) + (a - 2b - c)

[here is the problem]

=   -b                 combine like terms

result:  -b

(6.)  (4ab - 5bc + 6ac) - (6bc - 7ab - 8ac) - (10ab - bc - ac)

[here is the problem]

=   4ab - 5bc + 6ac - 6bc + 7ab + 8ac - 10ab + bc + ac

[multiply thru parentheses]

=   ab - 10bc + 15ac             combine like terms

result:  ab - 10bc + 15ac

(7.)  (x2 + y2 - z2) - (3z2 - 2x2 - 4y2) - (4y2 + x2 + z2)

[here is the problem]

=     x2 + y2 - z2 - 3z2 + 2x2 + 4y2 - 4y2 - x2 - z2

[multiply thru parentheses]

=   2x2 + y2 - 5z2             combine like terms

result:   2x2 + y2 - 5z2

(8.)  (x2 - 6x + 7) - (8x - 15 - x2) - (4x2 + 6x - 9) - (7x + 10)

[here is the problem]

=    x2 - 6x + 7 - 8x + 15 + x2 - 4x2 - 6x + 9 - 7x - 10

[multiply thru parentheses]

=    -2x2 - 27x + 21         combine like terms

result:   -2x2 - 27x + 21

(9.)

(a2 - 2ab + b2) - (2ab + a2 + b2) - (4a2 - 4ab - b2) - (a2 - b2)

[here is the problem]

=  a2 - 2ab + b2 - 2ab - a2 - b2 - 4a2 + 4ab + b2 - a2 + b2

[multiply thru parentheses]

=  -5a2 + b2              combine like terms

result:  -5a2 + b2

(10.)  (a + 2b) - (3b - 4c) - (5a - 7c) - (3b + 2d)

[here is the problem]

=   a + 2b - 3b + 4c - 5a + 7c - 3b - 2d   multiply thru

=   -4a - 4b + 11c - 2d     combine like terms

result:  -4a - 4b + 11c - 2d